From beauty to duty: aesthetics of nature and environmental ethics - Rolston, Holmes, 1932-2025, author; Ashgate Publishing, publisher (Colorado State University. Libraries, 2002)
In both environmental aesthetics and environmental ethics something of value is at stake. These are often connected: If beauty, then: duty. But not all duties are tied to beauties. Other premises, such as resource use or respect for life, might better yield duties. Human aesthetic capacities depend on aesthetic properties of value. Wildlife admirers focus on animal excellences. Biotic communities, ecosystems, have their integrities. In a participatory aesthetics, an appropriate admiration for nature transforms into our caring.

See De la beauté au devoir - French version: http://hdl.handle.net/10217/185272.
Keywords: conservation; scenic grandeur; environmental aesthetics; environmental ethics; biotic community; nature